Reestructuración técnico administrativa en la empresa Mobiliario Urbano Colombia LTDA. en la ciudad de Bogotá D.C. (2018)
The technical and administrative restructuring of the company Mobiliario Urbano Colombia LTDA. In the city of Bogota D.C, was based on data obtained from four studies. The first of these studies was the organizational diagnosis of the company; external and internal environmental analysis tools were used for this, such as sectoral analysis, auto-diagnosis of the company and chamber of commerce. The second study focused on the technical aspects, here the characteristics of the product were outlined along with the monthly master production plan.